1999
DOI: 10.2500/105065899782102863
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Neuropraxic Visual Loss Induced by Allergic Aspergillus Flavus Sinomycosis

Abstract: This work reports a patient with visual loss treated successfully with surgical removal of the Aspergillus flavus sinomycosis. Vision was partially reversed within hours after surgery before starting planned corticosteroid therapy. The patient's visual acuity continued to improve steadily until it became equal to that of the other eye. The immediate gain in vision and continued improvement without corticosteroid therapy suggest a new hypothesis for visual loss induced by allergic sinonasal Aspergillosis. Simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 8 publications
(9 reference statements)
0
13
0
Order By: Relevance
“…The condition can be challenging to treat but is fortunately rare, with only a few published reports. [5][6][7][8][9][10][11][12][13] We encountered optic nerve involvement leading to visual loss in 10 cases of allergic fungal sinusitis treated over a 10-year period from June 1997 to May 2007. Our experience with these cases is reported.…”
Section: Introductionmentioning
confidence: 99%
“…The condition can be challenging to treat but is fortunately rare, with only a few published reports. [5][6][7][8][9][10][11][12][13] We encountered optic nerve involvement leading to visual loss in 10 cases of allergic fungal sinusitis treated over a 10-year period from June 1997 to May 2007. Our experience with these cases is reported.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] Marple et al report rapid recovery of visual acuity after surgical decompression in patients with AFS and propose that AFS related visual loss is similar to visual loss with mucoceles concluding that surgical decompression should be the primary form of treatment for AFS related visual loss. 13 They considered visual loss related to compression to be more likely to recover than infectious and inflammatory conditions such as invasive bacterial orbital rhinosinusitis.…”
Section: Discussionmentioning
confidence: 95%
“…12 Our own review of the literature shows that 33 patients have been reported with partial or complete visual loss from AFS. 2,7,[12][13][14][15][18][19][20][21][22][23][24][25][26][27][28][29] Furthermore, 20 of the 33 patients have documented follow up of visual function, subjective or objective, after treatment. Sixteen of 20 patients showed improvement of their visual function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Visual loss associated with allergic fungal sinusitis is an uncommon finding (1.46% to 3.7 %) [29]. The pathophysiology of visual loss in patients with allergic fungal sinusitis has been proposed to be either through direct or indirect optic nerve compression, or through an inflammatory process that results in optic neuritis [29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%